Pengaruh Tingkat Pengangguran Terbuka, Indeks Pembangunan Manusia, dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan di Nusa Tenggara Timur - Siska Nofitiana; Syamsul Huda; Putra Perdana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Poverty is a problem of socio-economic conditions characterized by a lack of meeting basic needs. Indonesia still experiences poverty problems, especially in remote areas and among the informal sector workers. Poverty is influenced by several factors such as education, access to resources, financial management, wages and infrastructure development. The purpose of this research is to understand the influence of the open unemployment rate, human development index, and economic growth on poverty in the Regencies of East Sumba, Sabu Raijua, Central Sumba, and West Sumba from 2013 to 2022. This type of research is quantitative, and applies data secondary which is available on the BPS East Nusa Tenggara website. Eviews12 software is used to perform panel data regression. In this research, the Fixed-Effect Model (FEM) is considered the most appropriate. Based on the research results, the variables of open unemployment rate, Human Development Index, and economic growth simultaneously influence the poverty level. Specifically, the open unemployment rate has a significant effect on the poverty rate in the East Sumba, Sabu Raijua, Central Sumba and West Sumba regions from 2013 to 2022.